Frequency modulated song of the cicada Maua albigutta (Walker 1856) (Auchenorrhyncha: Cicadoidea) from South East Asia - Gogala, Matija (Scopolia, 2004)
The song and calling behaviour of the cicada Maua albigutta (Walker, 1856) from S.E. Asia is described. The majority of the investigations have been carried out in Endau Rompin National Park, Malaysia. The calling song comprises three main parts (A-C)with characteristic amplitude and, especially in the third part, with intense frequency modulation. The duration of the whole song is 38.2 +- 5.1 s and is often repeated without interruption many times in succession. Amplitude and frequency modulation is accompanied with movements of the abdomen and during frequency modulated calls also with changes of its shape. Songs from other localities (Kuala Lompat - Malaysia, Krui - Sumatra) are slightly different but clearly follow the same general pattern, and can be attributed with certainty to the same species.
Keywords: Maua albigutta; škržad; cicada; petje; song; acoustics; akustika; frekvenčna modulacija; frequency modulation